Maternal stress and birth outcomes among women with gestational diabetes mellitus (gdm) and healthy pregnant women - Rusdin, Izyana Mohd (Universiti Sains Malaysia, 2016)
Anxiety, depression and stress during pregnancy caused an adverse outcome at birth. Thus, this study was conducted to determine maternal stress level of woman with GDM and without GDM, to assess their birth outcome and to determine the relationship between maternal stress and birth outcome for both groups. A total about 42 pregnant women at more than 20 gestation weeks who were having GDM and 71 participants without GDM were recruited at Antenatal Clinic and Antenatal Ward, HUSM from January to April, 2016. All participants were given self-reported questionnaire for their sociodemographic and medical history. Perceived Stress Scale (PSS) questionnaire were used to assess maternal stress level. The weight and body composition were analysed by using bio-impedance analysis TANITA. Two weeks after the expected date of delivery, the participants were followed up through phone call to assess their birth outcome include gestation week at birth, birth weight, birth length, head circumference and mode of delivery. Ponderal index (kg/m3) were calculated manually. There was significant different in median value of fat percentage and pre-pregnancy BM1 between GDM and control group. The p-value for fat percentage was p = 0.012 (p-vahie <0.005) and p-value for prepregnancy BMI was p = 0.08 (p-value < 0.05), respectively. There were significant differences in median birth length between normal, median (IQR); 52 (3) and overweight participants, median (IQR); 50 (3), p-value is 0.017. There were no significant differences of PSS score between GDM and control group. There was significant, good and negative correlation between PSS score and head circumference of the babies (r = -0.321, p < 0.05). In conclusion, the maternal stress level between GDM and control group are equal. Regardless of that, there was association between maternal stress level and head circumference of baby.